NGHIÊN CỨU CHẾ TẠO VÀ THỬ HOẠT TÍNH KHÁNG KHUẨN CỦA DUNG DỊCH NANO BẠC SỬ DỤNG CHITOSAN LÀM CHẤT KHỬ/CHẤT ỔN ĐỊNH - Hoàng, Trần Vĩnh; Mạnh, Nguyễn Xuân; Kim Oanh, Vương Thị; Mai Hoa, Lê Thị; Lâm, Trần Đại (Vietnam Journal of Science and Technology, 2012)
SUMMARY STUDY ON SYNTHESIS AND ANTIBACTERIAL ACTIVITY OF SILVER NANOPARTICLE CONTAINING SOLUTION USING CHITOSAN AS REDUCING/ STABILIZING REAGENT Silver nanoparticles (AgNPs) were synthesized using chitosan as reducing and stabilizing agent via a green and facile method. First, AgNO3 was mixed with chitosan solution, then, the mixture was heated up to 85 – 95oC for a cerain period of time (2 - 48 h), in which AgNPs were  formed and homogeniously distributed/penetrated inside chitosan chains. AgNPs were characterized by XRD, IR, TEM and UV-vis methods. The obtained results confirmed that AgNPs, whose the  particle size of about 7 - 12 nm, were coated by chitosan layer, therefore are stable for at least 4 months without any significant agglomeration. Antibacterial test of AgNPs were investigated, confirming their enhanced antibacterial activities thanks to synergic properties of both AgNPs and chitosan. Keywords. Silver nanoparticles, chitosan, antibacterial activity